1998
DOI: 10.1038/sj.leu.2400914
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric acute myelogenous leukemia cells express IL-6 receptors and are sensitive to a recombinant IL6-Pseudomonas exotoxin

Abstract: We have studied IL-6 receptor (IL-6R) expression on AML cells from 15 pediatric patients by immunocytochemistry/flow cytometry, reverse-transcription polymerase chain reaction, and Scatchard analysis. High-affinity IL-6R were detected on leukemic cells from 12 (80%) patients. Binding sites per cell ranged from 140 to 3580 (median 920; mean 1240), with dissociation constants of 0.26 to 0.71 nM. We therefore assessed the in vitro sensitivity of IL-6R ؉ AML cells to treatment with a recombinant IL6-Pseudomonas ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This could explain the high numbers of positive samples (90%) in our study, as only CD34 + cases were included. IL-6Ra was found on the leukaemic cells of 80% of children with AML (35). G-CSFR was detected with a radiolabelled cytokine on 14/14 AML samples (36).…”
Section: Discussionmentioning
confidence: 98%
“…This could explain the high numbers of positive samples (90%) in our study, as only CD34 + cases were included. IL-6Ra was found on the leukaemic cells of 80% of children with AML (35). G-CSFR was detected with a radiolabelled cytokine on 14/14 AML samples (36).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it was demonstrated that AML cells produce soluble IL-6 receptor, which might explain the reduced serum levels of biologically active IL-6 detected in our study. 42,43 Since tumor cells are often a good cellular source of chemokines, 44 it was verified whether leukocytic cell lines produce PARC in response to various endogenous or exogenous stimuli. It was found that THP-1, HL60, Sup-T1, and MT4 cells did not secrete a detectable amount of PARC after stimulation with the cytokines IL-1, IL-4, IL-10, or IFN-␥, nor after induction with virus, dsRNA, endotoxin, enterotoxin, phorbol ester, or lectin.…”
Section: Discussionmentioning
confidence: 99%
“…This chimeric toxin was potently cytotoxicity against a variety of different tumor cell lines displaying IL6Rs including multiple myeloma, prostate, hepatoma and carcinoma [139]. In two studies of pediatric cancer, IL6-PE was cytotoxic for freshly isolated (IL6R-expressing) patient cells diagnosed with either Acute Myelogenous Leukemia or Acute Lymphoblastic Leukemia [140,141]. The killing was roughly proportional to the number of receptors per cell.…”
Section: Targeting Interleukin-6 Receptor (Il6r)mentioning
confidence: 99%